Series of Fourteen Cases of Topical Imiquimod 5% in Lentigo Maligna: Treatment Modalities and Clues for Detecting Recurrences - I. Poveda-Montoyo; P. Álvarez-Chinchilla; L. Schneller-Pavelescu; P. Hispán-Ocete; J. Bañuls-Roca (Elsevier, 2022)
Topical imiquimod has been used off-label as monotherapy or adjuvant treatment for lentigo maligna. Our aim is to describe treatment modalities, clinical outcomes, and management of recurrence in patients receiving imiquimod for lentigo maligna.Patients from our unit with lentigo maligna or lentigo maligna melanoma treated with imiquimod 5% as monotherapy or in combination with surgery were included in this study.Fourteen cases were recruited (85.7% lentigo maligna and 14.3% lentigo maligna melanoma). Eight patients (57.1%) received imiquimod without surgery, and six (42.9%) underwent narrow excision before beginning treatment. During the follow-up period, pigmentation reappeared in 6 patients (4 postinflammatory hyperpigmentation and 2 relapses). Relapses were managed with very narrow excision (1 mm margin) and retreatment with imiquimod 5%.All imiquimod modalities showed well-tolerated side effects and low recurrence rates, with long periods of follow-up. Imiquimod appears to be a versatile option for treating LM in suitable candidates. Resumen: Imiquimod tópico ha sido utilizado como monoterapia o tratamiento adyuvante fuera de indicación para el lentigo maligno (LM). Nuestro objetivo es describir las modalidades de tratamiento, los resultados clínicos y el manejo de la recidiva en los pacientes que reciben imiquimod para lentigo maligno.Se incluyó en este estudio a los pacientes de nuestra unidad con lentigo maligno o lentigo maligno melanoma tratados con imiquimod 5% en régimen de monoterapia o junto con cirugía.Se seleccionaron 14 casos (el 85,7% de lentigo maligno y el 14,3% de lentigo maligno melanoma). Ocho pacientes (57,1%) recibieron imiquimod sin cirugía, y seis (42,9%) fueron sometidos a resección antes de iniciar el tratamiento. Durante el periodo de seguimiento, reapareció la pigmentación en seis pacientes (cuatro con hiperpigmentación postinflamatoria y dos recidivas). Las recidivas fueron tratadas con un margen de resección muy estrecho (1 mm) y retratamiento con imiquimod 5%.Todas las modalidades de imiquimod reflejaron buena tolerancia de efectos secundarios y bajas tasas de recidiva. Imiquimod parece ser una opción muy versátil para tratar LM en candidatos idóneos.